Hemoglobin A1c level is a prognostic factor for locoregional recurrence in stage III non‐small cell lung cancer patients treated with radiotherapy - Moonkyoo Kong (Wiley, 2021)
Abstract Background The level of hemoglobin A1c (HbA1c) might be associated with the severity of tumor hypoxia in patients with cancer. Here, we evaluated the association between the level of HbA1c and survival outcome in stage III non‐small cell lung cancer patients treated with radical radiotherapy. Methods We retrospectively analysed the clinical data of 104 patients with lung cancer treated with radiotherapy. The HbA1c levels of all patients were checked 1 week before the start of radiotherapy. Survival outcomes were analysed according to the HbA1c level. Results The 1‐, 2‐, and 3‐year locoregional recurrence‐free survival rates were 88.3%, 68.8%, and 63.0%, respectively, in the patient group with HbA1c levels ≤6% and 75.5%, 54.4%, and 41.8%, respectively, in the patient group with HbA1c levels >6% (p = 0.015). The HbA1c level remained a significant prognostic factor for locoregional recurrence‐free survival on multivariable analysis (hazard ratio = 2.014, 95% confidence interval = 1.088–3.726, p = 0.026). Conclusions Pretreatment HbA1c level is a significant prognostic factor for locoregional recurrence‐free survival in patients with stage III non‐small cell lung cancer treated with radical radiotherapy. Routine monitoring of pretreatment HbA1c levels and aggressive glycemic control may be considered to prevent the development of locoregional recurrence in these patients.